Molding material

The molding material with cellulose fibers and a resin having a specific molecular weight distribution addresses thermal degradation issues, ensuring high mechanical strength in molded products despite heat history, suitable for various applications.

JP2025006305APending Publication Date: 2025-01-17SEIKO EPSON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023107012
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Conventional composite materials experience a decrease in mechanical strength due to thermal degradation during molding processes, particularly when molded products or gate materials are melted, pelletized, and molded again.

Method used

A molding material comprising cellulose fibers and a resin, where the resin includes a polyester elastomer and a highly polar polyester, with a specific molecular weight distribution characterized by a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 below, and the area value at maximum value 2 being smaller than at maximum value 1, to maintain mechanical strength despite thermal decomposition.

Benefits of technology

The material maintains excellent mechanical strength, including Charpy impact strength and flexural modulus, even with a history of molding heat, making it suitable for applications such as containers, sheets, and appliance housings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006305000001
    Figure 2025006305000001
  • Figure 2025006305000002
    Figure 2025006305000002
  • Figure 2025006305000003
    Figure 2025006305000003
Patent Text Reader

Abstract

To provide a molding material that achieves excellent mechanical strength even in the presence of molding-related thermal stress.SOLUTION: A molding material according to one embodiment of the present disclosure is a molding material containing cellulose fibers and a resin, and the resin includes a polyester-based elastomer and a highly polar polyester. In a molecular weight distribution curve by the GPC method, the resin has a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 at a weight average molecular weight less than that at the maximum value 2, and an area value in the maximum value 2 is smaller than an area value in the maximum value 1.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a molding material. [Background technology]

[0002] Conventionally, molding materials containing cellulose fibers and resins have been known. For example, Patent Document 1 discloses a cellulose composite resin containing cellulose fibers, a base resin such as an olefin resin, and a rubber-containing polymer. The rubber-containing polymer is composed of an aliphatic hydrocarbon or aromatic hydrocarbon having only a specific functional group. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-033541 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the mechanical strength of the composite materials of the prior art can be reduced if they have a thermal history of molding, for example, when a molded product or a gate material used during molding is melted, pelletized, and then molded again. [Means for solving the problem]

[0005] One aspect of the molding material according to the present invention is A molding material comprising cellulose fibers and a resin, The resin includes a polyester-based elastomer and a highly polar polyester, The resin has a molecular weight distribution curve by a GPC method, which has a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 at a weight average molecular weight lower than the maximum value 2, The area value at the local maximum value 2 is smaller than the area value at the local maximum value 1. [Brief description of the drawings]

[0006] [Figure 1] FIG. 1 shows the composition of raw materials, molding method, and evaluation results of molded products for the molding materials of each Example and Comparative Example (Table 1). [Diagram 2] FIG. 2 shows the composition of raw materials, molding method, and evaluation results of molded products for the molding materials of each Example and Comparative Example (Table 2). [Diagram 3] FIG. 3 shows the composition of raw materials, molding method, and evaluation results of molded products for the molding materials of each Example and Comparative Example (Table 3). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, an embodiment of the present invention will be described. The embodiment described below is an example of the present invention. The present invention is not limited to the following embodiment, and includes various modified forms that are implemented within the scope that does not change the gist of the present invention. Note that not all of the configurations described below are necessarily essential configurations of the present invention.

[0008] 1.Molding material A molding material according to one embodiment of the present invention is a molding material comprising cellulose fibers and a resin, the resin comprising a polyester-based elastomer and a highly polar polyester, and in a molecular weight distribution curve measured by a GPC method, the resin has a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 below the weight average molecular weight at maximum value 2, and the area value at maximum value 2 is smaller than the area value at maximum value 1.

[0009] When a molded product or gate material used in molding is melted and pelletized before being molded again, the resin in the molding material will degrade due to thermal decomposition and its various properties will deteriorate. Low-melting resins that melt at less than 200°C are particularly susceptible to thermal decomposition.

[0010] Therefore, the inventors conducted extensive research and found that when a resin contains an appropriate amount of high molecular weight components, the resin has excellent mechanical strength, such as Charpy impact strength and flexural modulus, even when the resin has a molding thermal history.

[0011] The molding material can be molded by known molding methods such as injection molding and press processing. Molded products made from the molding material are suitable as replacements for polystyrene and the like for various containers, sheets, and housings for office equipment such as printers and home appliances.

[0012] The various raw materials contained in the molding material will be described below.

[0013] 1.1 Cellulosic fibers The molding material according to the present embodiment contains cellulose fibers. The cellulose fibers function as a filler in the molded product, and contribute to increasing the bulk of the molding material and improving the physical properties, such as the strength, of the molded product.

[0014] Cellulose fibers are derived from plants and are relatively abundant natural materials. Therefore, the use of cellulose fibers promotes a reduction in the environmental load compared to the use of synthetic fibers. Cellulose fibers are also advantageous in terms of raw material procurement and cost. Furthermore, among various fibers, cellulose fibers have a high theoretical strength, and contribute to improving the strength of molded products. In addition to using virgin pulp as cellulose fibers, waste paper, old cloth, etc. may be reused. Furthermore, commercially available products may be used as cellulose fibers.

[0015] The cellulose fibers are mainly made of cellulose, but may contain components other than cellulose, such as hemicellulose and lignin. The cellulose fibers may be subjected to a process such as bleaching.

[0016] From the viewpoint of improving the appearance of the surface of a molded article, the average fiber length of the cellulose fibers is preferably less than 500 μm, and more preferably less than 50 μm. The average fiber length of the cellulose fibers is determined by a method in accordance with ISO 16065-2:2007.

[0017] The content of cellulose fiber is preferably 9% by mass or more, more preferably 18% by mass or more, even more preferably 27% by mass or more, even more preferably 36% by mass or more, and particularly preferably 45% by mass or more, based on the total mass of the molding material. The content of cellulose fiber is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less, based on the total mass of the molding material. When the content of cellulose fiber is within the above range, good mechanical strength tends to be obtained even when there is a molding heat history.

[0018] 1.2 Resin The molding material according to the present embodiment contains a resin, and the resin includes a polyester-based elastomer and a highly polar polyester.

[0019] Polyester elastomers play a role as a resin matrix and ensure the impact resistance (toughness) of the molded body. However, they have low compatibility with cellulose fibers, and the two tend to peel off at the interface. Therefore, by using a highly polar polyester, the cellulose fibers and polyester This functions as a compatible solvent with the base elastomer and can suppress interfacial peeling.

[0020] The resin content is preferably equal to or less than the above-mentioned cellulose fiber content, in which case better mechanical strength tends to be obtained even in the case where there is a molding heat history.

[0021] 1.2.1 Polyester elastomers Polyester-based elastomers have thermoplastic properties, and when a molded product is produced from the molding material, they melt and bond the cellulose fibers together. In addition, polyester-based elastomers, together with cellulose fibers, are responsible for the physical properties of the molded product. In particular, polyester-based elastomers increase the toughness of the molded product and improve its impact strength. Furthermore, polyester-based elastomers have the potential to be produced and used as bioplastics in the future, and are also expected to promote the reduction of environmental impact.

[0022] The polyester elastomer preferably contains, as raw material monomers, an alkyldicarboxylic acid or phthalic acid having an alkylene group with a carbon number of 2 to 8, and an alkylene diol having an alkylene group with a carbon number of 2 to 8. When the polyester elastomer contains the above raw material monomers, better mechanical strength tends to be obtained even when the polyester elastomer has a molding heat history. The polyester elastomer is preferably produced by copolymerizing the above two raw material monomers. The copolymerization can be carried out by a known synthesis method.

[0023] Examples of the alkyl dicarboxylic acid include linear saturated aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. These alkyl dicarboxylic acids may have a substituent in the molecular structure. It is preferable to use one or more of these for the synthesis of polyester elastomers.

[0024] The phthalic acid may have a substituent in the molecular structure.

[0025] Examples of the alkylene diol include dihydric alcohols such as 1,2-ethanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, and 1,8-octanediol. It is preferable to use one or more of these for the synthesis of polyester elastomers. The above-mentioned three types of raw material monomers are relatively easy to obtain and can be used for industrial or commercial purposes.

[0026] The polyester elastomer may contain other raw material monomers in addition to the above-mentioned raw material monomers. The other raw material monomers include styrene, butadiene, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, acetonitrile, isobutylene, isoprene, and ethylene, and it is preferable to use one or more of these. When such other raw material monomers are contained, even if there is a molding heat history, better mechanical strength tends to be obtained.

[0027] When other raw material monomers are incorporated into the polyester elastomer, the total mole number of the other raw material monomers is preferably 1% or more and less than 50% of the total mole number of the raw material monomers, which tends to provide better mechanical strength even when the elastomer has a molding heat history.

[0028] The polyester elastomer may be a commercially available product. Examples of the commercially available products include ES-A60NX, E-D27N, E-D42N, and ES series ( The above-mentioned product names are examples of the polyester elastomer. One or more of these may be used as the polyester elastomer.

[0029] Here, the presence or absence of a polyester-based elastomer in the molding material or in the form of a molded article can be determined by the following physical property analysis and component analysis.

[0030] First, the presence or absence of a component with a composite modulus of elasticity of 100 MPa or less is confirmed by physical property analysis. When the above component is contained, it is determined that an elastomer component is contained. Specifically, for example, a scanning probe microscope NX20 from Park Systems Japan is used to measure the cross section of the molding material or molded body in contact mode. This makes it possible to confirm the presence or absence of a component with a composite modulus of elasticity of 100 MPa. A known nanoindenter may also be used to confirm the presence or absence of an elastomer component.

[0031] Next, a qualitative analysis is performed using a combination of pyrolysis gas chromatography mass spectrometry (GC-MS) and Fourier transform infrared spectroscopy (FT-IR) to determine whether the elastomer component is a polyester-based elastomer. The pyrolysis GC-MS method is an analytical method that identifies various fragments generated by pyrolyzing a sample. The FT-IR method is an analytical method that identifies the molecular structure of a sample from its infrared absorption spectrum. These methods make it possible to identify the molecular structure of a sample.

[0032] For the pyrolysis GC-MS method, for example, a multi-shot pyrolyzer EGA / PY-3030D manufactured by Frontier Labs and a GC / MS 5975 equipped with the device manufactured by Agilent Technologies are used. For the FT-IR method, for example, a Nicolet® 380 Continuμm® manufactured by Thermo Fisher Scientific is used.

[0033] The content of the polyester-based elastomer is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on the total mass of the molding material. The content of the polyester-based elastomer is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less, based on the total mass of the molding material. When the content of the polyester-based elastomer is within the above range, even if there is a molding heat history, better mechanical strength tends to be obtained.

[0034] The content of the polyester elastomer is preferably 25% by mass or more (more preferably 50% by mass or more, even more preferably 75% by mass or more, and particularly preferably 100% by mass or more) relative to the content of the highly polar polyester described below, and the total content of the polyester elastomer and the highly polar polyester is preferably equal to or less than the content of the cellulose fiber described above. In such a case, even if there is a molding heat history, better mechanical strength tends to be obtained.

[0035] The content of the polyester elastomer is preferably 400% by mass or less, more preferably 300% by mass or less, further preferably 250% by mass or less, and particularly preferably 200% by mass or less, based on the content of the highly polar polyester described below. In such a case, even if there is a molding heat history, better mechanical strength tends to be obtained.

[0036] 1.2.2 Highly polar polyester The highly polar polyester improves the compatibility between the cellulose fiber and the polyester elastomer, which enhances the wettability of the polyester elastomer to the cellulose fiber, and mainly improves the bending strength of the molded product.

[0037] The highly polar polyester has a molecular structure with a relatively high polarity, and preferably has a repeating structure derived from the raw material monomer with 2 carbon atoms and 1 or more oxygen atoms. In such a case, even if there is a molding heat history, better mechanical strength tends to be obtained. In detail, the highly polar polyester preferably contains raw material monomers such as lactic acid, hydroxybutyric acid, oxysuccinic acid, citric acid, malonic acid, succinic acid, serine, threonine, acrylic acid, methyl acrylate, and vinylacetic acid. These are relatively easy to obtain and can be used for industrial or commercial purposes.

[0038] Specifically, the highly polar polyester preferably contains one or more of polylactic acid, polyhydroxybutyric acid, polyacrylic acid, polymethyl acrylate, and polyvinyl acetate. The highly polar polyester may also be a copolymer such as polyethylene succinic acid or P3HBH (3-hydroxy(butyrate-co-hexanoate)). Among these, the highly polar polyester preferably contains one or more of polylactic acid and polyhydroxybutyric acid. Such compounds are biodegradable and can reduce the environmental load, and tend to provide better mechanical strength even when there is a molding heat history. Commercially available products may be used as the highly polar polyester.

[0039] The content of the highly polar polyester is preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, particularly preferably 15% by mass or more, and more particularly preferably 20% by mass or more, based on the total mass of the molding material. The content of the highly polar polyester is preferably 90% by mass or less, more preferably 70% by mass or less, even more preferably 50% by mass or less, and particularly preferably 40% by mass or less, based on the total mass of the molding material. When the content of the highly polar polyester is within the above range, even if there is a molding heat history, better mechanical strength tends to be obtained.

[0040] 1.2.3 Other resins The resin contained in the molding material according to the present embodiment may contain a resin other than the polyester-based elastomer and the highly polar polyester. Examples of such resins include olefin-based resins such as polyethylene and polypropylene, urethane-based resins, and acrylic-based resins.

[0041] 1.2.4 Molecular weight distribution The resin contained in the molding material according to this embodiment has, in a molecular weight distribution curve by GPC method, a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 below the weight average molecular weight at maximum value 2, and the area value at maximum value 2 is smaller than the area value at maximum value 1. In this way, by having the resin have an appropriate amount of high molecular weight components, it is possible to maintain mechanical strength even if thermal decomposition of the resin occurs due to the molding heat history.

[0042] The GPC method is a gel permeation chromatography method, and can be measured, for example, by the following procedure. A GPC device (ACQUITY APC, manufactured by Waters) with two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) connected in series is used as the measurement device. The measurement sample (molding material) is dissolved in chloroform as the eluent, filtered through a filter with a pore size of 0.45 μm, and the dissolved components are subjected to GPC analysis to obtain the molecular weight distribution curve of the resin. Here, the column temperature is set to 40°C, and an IR detector is used as the detector. In addition, polystyrene (manufactured by Agilent) is used as the standard sample.

[0043] The peak calculation method can be, for example, as follows. The chromatogram is regarded as a linear function, and the position where the slope becomes 0 when the function is differentiated is regarded as the peak top. The chromatogram is regarded as a linear function, and the position where the slope becomes 0 when the function is differentiated is regarded as the peak boundary. The peak is divided vertically from the peak boundary position, and the area value of each peak is calculated. Note that if the peak is sufficiently large, If the peaks are separated, the area value may be treated as a single peak. If the two overlapping peaks are clearly distinguishable, they may be treated as a shoulder peak, and the area value may be calculated by drawing a straight line through the base of the smaller peak. Furthermore, the area of ​​each peak may be calculated using peak separation software. However, the agreement rate must be 90% or more.

[0044] The resin contained in the molding material according to this embodiment has a maximum value 2 at a weight average molecular weight of 100,000 or more in a molecular weight distribution curve by GPC method, but the weight average molecular weight is preferably 110,000 or more, more preferably 120,000 or more, and even more preferably 130,000 or more. The maximum value 2 is preferably at a weight average molecular weight of 500,000 or less, more preferably 400,000 or less, and even more preferably 350,000 or less. If the maximum value 2 is within the above range, better mechanical strength tends to be obtained even in the case of a molding heat history.

[0045] The resin contained in the molding material according to this embodiment has a maximum value 1 in the molecular weight distribution curve by the GPC method, which is less than the weight average molecular weight at the maximum value 2, and the maximum value 1 is preferably at a weight average molecular weight of 150,000 or less, more preferably at 120,000 or less, and even more preferably at 100,000 or less. The maximum value 1 is preferably at a weight average molecular weight of 30,000 or more, more preferably at 50,000 or more, and particularly preferably at 60,000 or more. If the maximum value 1 is within the above range, better mechanical strength tends to be obtained even when there is a molding heat history.

[0046] Here, (weight average molecular weight at maximum value 2) / (weight average molecular weight at maximum value 1) is preferably more than 1.0 and not more than 5.0, more preferably 1.1 or more and not more than 4.0, even more preferably 1.2 or more and not more than 3.5, particularly preferably 1.5 or more and not more than 3.0, and even particularly preferably 1.6 or more and not more than 2.5. In this case, even if there is a molding thermal history, better mechanical strength tends to be obtained.

[0047] 1.3 Crosslinking Agent The molding material according to the present embodiment may further contain a crosslinking agent. By containing a crosslinking agent, it is easy to adjust the molecular weight distribution of the resin, and therefore even if there is a molding heat history, better mechanical strength tends to be obtained.

[0048] The crosslinking agent is preferably one having a reactive group capable of crosslinking with polyester. More specifically, the crosslinking agent is preferably one having a reactive group selected from carbodiimide, amine, epoxy, isocyanate, protected isocyanate, carboxylic anhydride, and carboxylic acid. Crosslinking agents having such reactive groups can preferably react with polyester elastomers and highly polar polyesters, and are easy to adjust the molecular weight distribution in the resin, and therefore tend to provide better mechanical strength even when there is a molding heat history.

[0049] The crosslinking agent may be a commercially available product, and examples thereof include Metablen P-1901 (manufactured by Mitsubishi Chemical Corporation), Deconal EX-321 (manufactured by Nagase ChemteX Corporation, trimethylolpropane polyglycidyl ether), Deconal EX-211 (manufactured by Nagase ChemteX Corporation, neopentyl glycol diglycidyl ether), Duranate E402-B80B (Asahi Kasei Corporation, isocyanate), Carbodilite HMV-5CA-LC (Nisshinbo Chemical Inc.), Carbodilite Elastostab H01 (Nisshinbo Chemical Inc.), and Sigma-Aldrich: Product No. 188050 (Merck, poly(ethylene-alt-maleic anhydride)).

[0050] The content of the crosslinking agent is preferably 1% by mass or more, more preferably 2% by mass or more, based on the total mass of the molding material. The content of the crosslinking agent is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 6% by mass or less, based on the total mass of the molding material. When the content of the agent is within the above range, better mechanical strength tends to be obtained even when there is a molding thermal history.

[0051] The content of the crosslinking agent is preferably 3 parts by mass or more and 20 parts by mass or less, more preferably 5 parts by mass or more and 15 parts by mass or less, and particularly preferably 7 parts by mass or more and 13 parts by mass or less, when the total content of the resins is taken as 100 parts by mass. When the content of the crosslinking agent is within the above range, better mechanical strength tends to be obtained even when there is a molding heat history.

[0052] 1.4 Flame retardants The molding material according to the present embodiment may contain a flame retardant. Known substances can be used as the flame retardant. Examples of the flame retardant include inorganic flame retardants such as antimony compounds, metal hydroxides, nitrogen compounds, and boron compounds, and organic flame retardants such as bromine compounds and phosphorus compounds.

[0053] As the flame retardant, commercially available products may be used, and examples thereof include Rabitol FP-110 (a phosphazene-based flame retardant manufactured by Mitsui Fine Chemicals, Inc.) and Exolit OP1230 (a phosphate-based flame retardant manufactured by Clariant).

[0054] The content of the flame retardant is preferably 1% by mass or more and 15% by mass or less, more preferably 1% by mass or more and 10% by mass or less, and even more preferably 3% by mass or more and 8% by mass or less, based on the total mass of the molding material. When the content of the flame retardant is within the above range, the flame retardancy of the molded product is improved, and better mechanical strength tends to be obtained even when the molded product has a molding heat history.

[0055] The content of the flame retardant is preferably 1 part by mass to 20 parts by mass, more preferably 5 parts by mass to 20 parts by mass, and even more preferably 8 parts by mass to 15 parts by mass, when the total content of the cellulose fiber, the polyester elastomer, and the high polarity polyester is taken as 100 parts by mass. When the content of the flame retardant is within the above range, the flame retardancy of the molded article is improved, and better mechanical strength tends to be obtained even when the molded article has a thermal molding history.

[0056] 1.5 Other ingredients The molding material according to this embodiment may contain other components, such as a colorant, an insect repellent, an anti-fungal agent, an antioxidant, an ultraviolet absorbing agent, an aggregation inhibitor, and a mold release agent.

[0057] 2. Manufacturing method of molding material A method for producing the molding material will now be described. A known method can be applied to produce the molding material. Specifically, for example, the method described below can be applied.

[0058] First, the above-mentioned raw materials are kneaded in a single-screw or twin-screw kneader to form a strand shape, and then pelletized to form a pellet-shaped molding material.

[0059] The following method may also be used as a manufacturing method for the molding material. First, waste paper or pulp material is roughly crushed in a shredder device to produce cellulose fibers. Then, the cellulose fibers, polyester elastomer, and high polarity polyester are weighed and kneaded. Next, the kneaded raw materials are piled up in air to produce a sheet-like pile. Since the pile contains a lot of air and has a low density, it is compressed in a calendar device to remove the air and increase the density. Next, the pile is heated in a non-contact manner using a heating furnace, and then hot-pressed in a heat press device.

[0060] In the heating furnace and heat press device, it is preferable to heat at a temperature about 20° C. higher than the melting temperature of the polyester elastomer and the highly polar polyester, which tends to form a sheet in which the raw materials are dispersed with less bias.

[0061] Next, the sheet is cut into a desired shape by a shredder device to obtain a pellet-shaped molding material. The desired shape of the molding material is not particularly limited, but is generally a cube of 2 mm 3 to 5 mm 3. The molding material is manufactured by the above method. Note that the manufacturing method of the molding material is not limited to the above.

[0062] 3. Working Example The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0063] 3.1 Preparation of molding materials and test specimens Figures 1 to 3 (Tables 1 to 3) show the raw material compositions, molding methods, and evaluation results of molded products for the molding materials of each Example and Comparative Example. In the composition columns of Figures 1 to 3 (Tables 1 to 3), the units of values ​​are parts by mass, and columns with no values ​​indicate that the component is not contained.

[0064] The descriptions in Figures 1 to 3 (Tables 1 to 3) are supplemented as follows. <Polyester elastomer> Product name: ES-A60NX, Aronkasei Co., Ltd. <Olefin elastomer> EPDM (Ethylene Propylene Diene Rubber) (Product Name: NOLDEL® 3720P, Dow Toray) <Highly polar polyester> Polylactic acid (Terramac (registered trademark) TE-2000, Unitika Co., Ltd.) Polyhydroxyalkane (P3HBH) (product name Green Planet (registered trademark), Kaneka Corporation) <Cellulose fiber> Product name: Guaiba BEKP, CMPC <Crosslinking Agent> Crosslinking agent 1 (Metabrene P-1901, manufactured by Mitsubishi Chemical Corporation) Crosslinking agent 2 (Deconal EX-321, Nagase ChemteX Corporation, trimethylolpropane polyglycidyl ether) Crosslinking agent 3 (Deconal EX-211, manufactured by Nagase ChemteX Corporation, neopentyl glycol diglycidyl ether) Crosslinking agent 4 (Duranate E402-B80B, Asahi Kasei Corporation, isocyanate) Crosslinking agent 5 (Carbodilite HMV-5CA-LC, Nisshinbo Chemical Inc.) Crosslinking agent 6 (Carbodilite Elastostab H01, Nisshinbo Chemical Co., Ltd.) Crosslinker 7 (Sigma-Aldrich: product no. 188050, Merck, poly(ethylene-alt-maleic anhydride) <Flame retardants> Flame retardant 1 (Lavitol FP-110, manufactured by Mitsui Fine Chemicals, Inc., a phosphazene-based flame retardant) Flame retardant 2 (Exolit OP1230, Clariant, phosphate ester flame retardant)

[0065] Molding materials according to each Example and Comparative Example were produced according to the compositions shown in Figures 1 to 3 (Tables 1 to 3). Specifically, polyester-based elastomers, highly polar polyesters, olefin-based elastomers (other elastomers), cellulose fibers, crosslinking agents, etc. were weighed.

[0066] Next, the mixture was put into a Technovel twin-screw mixer KZW15TW-45MG and mixed. The mixing conditions were a maximum heating temperature of 180°C and an extrusion discharge rate of 1 kg / hr. The mixture was then processed into a strand shape and pelletized into a pelletized molding material using a pelletizer.

[0067] The weight average molecular weight of the molding material obtained above was measured by the GPC method. Specifically, a GPC device (ACQUITY APC, manufactured by Waters) with two separation columns (TSKgel SuperHZM-H, manufactured by Tosoh) connected in series was used as the measuring device. The measurement sample (molding material) was dissolved in chloroform as an eluent, filtered through a filter with a pore size of 0.45 μm, and the dissolved components were subjected to GPC analysis to obtain a molecular weight distribution curve of the resin. Here, the column temperature was set to 40° C., an IR detector was used as the detector, and polystyrene (manufactured by Agilent) was used as the standard sample. The peak calculation method was performed as described above.

[0068] Molding materials according to each Example and Comparative Example were used to perform molding by injection molding or press processing. Specifically, the heating temperature of the molding material was 200°C for both injection molding and press processing. The injection molding device used was Nissei Plastic Industrial Co., Ltd.'s THX40-5V, and the press processing device used was Towa Seiki Co., Ltd.'s hydraulic press PHKS-40ABS.

[0069] Here, in the molding history of Figures 1 to 3 (Tables 1 to 3), "repellet once" means that the above-mentioned molding process was re-pelletized and molding was carried out again in the same manner as above, and "first time" means that molding was carried out only once without re-pelletization. Also, in the crosslinking agent addition step of Figures 1 to 3 (Tables 1 to 3), "repellet" means that the above-mentioned molding process was added when the material was re-pelletized, and "first time" means that the material was added only when the raw materials were mixed. In this manner, test pieces in each of the examples and comparative examples were obtained.

[0070] 3.2 Evaluation Test Charpy impact strength was used as an index of impact strength, and the test method was carried out in accordance with ISO 179 (JIS K7111). The shape of the test piece was a rectangular plate with a long side of 80 mm ± 2 mm, a short side of 4.0 mm ± 0.2 mm, and a thickness of 10.0 mm ± 0.2 mm. The test device used was an Impact Tester IT manufactured by Toyo Seiki Seisakusho. In the Charpy impact test, the hammer weight was 4J (WR 2.14 N / m), the lifting angle was 150°, the notch remaining width was 8.0 mm ± 0.2 mm, and the notch angle was 45°.

[0071] The bending properties were used as an index of bending strength, and the test method was carried out in accordance with ISO 178 (JIS K7171). The shape of the test piece was a rectangular plate with a long side of 80 mm ± 2 mm, a short side of 10.0 mm ± 0.2 mm, and a thickness of 4.0 mm ± 0.2 mm. The test equipment used was an Instron 68TM-30, and the test was carried out with a support distance of 64 mm.

[0072] For each level of test result obtained, the strength of the molded product was judged according to the following criteria. (Judgment criteria) A: Charpy impact strength is 7kJ / m 2 and the flexural modulus is 3000 MPa or more. B: Charpy impact strength is 4kJ / m 2 or higher, and the flexural modulus is 1500 MPa or higher (excluding the range of A rating). C: Charpy impact strength is 4kJ / m2 or higher, or the flexural modulus is 1500 MPa or higher (excluding the ranges rated A and B). D: Charpy impact strength is 4kJ / m 2 and the flexural modulus is 1,500 MPa or less (excluding the ranges of B and C). E: Not moldable.

[0073] 3.3 Evaluation results The evaluation results are shown in Figures 1 to 3 (Tables 1 to 3).

[0074] From the results shown in Figures 1 to 3 (Tables 1 to 3), it was found that the molding materials of each example, which contain cellulose fibers and a resin, where the resin contains a polyester-based elastomer and a highly polar polyester, and in a molecular weight distribution curve measured by GPC method, the resin has a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 below the weight average molecular weight at maximum value 2, and the area value at maximum value 2 is smaller than the area value at maximum value 1, can obtain good mechanical strength even when they have a molding thermal history.

[0075] In contrast, the molding materials according to the comparative examples not satisfying the above-mentioned configuration did not provide good mechanical strength when subjected to a molding thermal history.

[0076] The following can be derived from the above-described embodiment.

[0077] One embodiment of the molding material is A molding material comprising cellulose fibers and a resin, The resin includes a polyester-based elastomer and a highly polar polyester, The resin has a molecular weight distribution curve by a GPC method, which has a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 at a weight average molecular weight lower than the maximum value 2, The area value at the local maximum value 2 is smaller than the area value at the local maximum value 1.

[0078] In one embodiment of the molding material, The molding material may further contain a crosslinking agent.

[0079] In any one of the embodiments of the molding material, The crosslinker may have reactive groups selected from carbodiimide, amine, epoxy, isocyanate, protected isocyanate, carboxylic acid anhydride, carboxylic acid.

[0080] In any one of the embodiments of the molding material, the content of the polyester-based elastomer is 25% by mass or more relative to the content of the highly polar polyester, The total content of the polyester elastomer and the highly polar polyester may be equal to or less than the content of the cellulose fibers.

[0081] In any one of the embodiments of the molding material, The content of the polyester elastomer may be 400% by mass or less based on the content of the highly polar polyester.

[0082] In any one of the embodiments of the molding material, The polyester elastomer may contain, as raw material monomers, an alkyldicarboxylic acid or phthalic acid having an alkylene group with 2 to 8 carbon atoms, and an alkylene diol having an alkylene group with 2 to 8 carbon atoms.

[0083] In any one of the embodiments of the molding material, The polyester-based elastomer contains other raw material monomers in addition to the raw material monomers, The other raw material monomers include styrene, butadiene, acrylic acid, acrylic acid esters, The copolymer may be one or more of methacrylic acid, methacrylic acid esters, acetonitrile, isobutylene, isoprene, and ethylene.

[0084] In any one of the embodiments of the molding material, The highly polar polyester may have a repeating unit derived from the raw material monomer in which the number of oxygen atoms is 1 or more for every 2 carbon atoms.

[0085] In any one of the embodiments of the molding material, The highly polar polyester may include one or more of polylactic acid and polyhydroxybutyric acid.

[0086] In any one of the embodiments of the molding material, The cellulose fibers may have an average fiber length of less than 500 μm.

[0087] The present invention is not limited to the above-described embodiment, and various modifications are possible. For example, the present invention includes a configuration that is substantially the same as the configuration described in the embodiment, for example, a configuration that has the same function, method, and result, or a configuration that has the same purpose and effect. The present invention also includes a configuration in which non-essential parts of the configuration described in the embodiment are replaced. The present invention also includes a configuration that has the same action and effect as the configuration described in the embodiment, or a configuration that can achieve the same purpose. The present invention also includes a configuration in which publicly known technology is added to the configuration described in the embodiment.

Claims

1. A molding material comprising cellulose fibers and a resin, The resin includes a polyester-based elastomer and a highly polar polyester, In a molecular weight distribution curve according to a GPC method, the resin has a maximum value 2 at a weight average molecular weight of 100,000 or more and a maximum value 1 at a weight average molecular weight lower than the maximum value 2, A molding material, wherein the area value at the maximum value 2 is smaller than the area value at the maximum value 1.

2. The molding material according to claim 1 , further comprising a crosslinking agent.

3. 3. The molding material of claim 2, wherein the crosslinker has reactive groups selected from carbodiimide, amine, epoxy, isocyanate, protected isocyanate, carboxylic acid anhydride, and carboxylic acid.

4. the content of the polyester-based elastomer is 25% by mass or more relative to the content of the highly polar polyester, The molding material according to claim 1 or 2, wherein a total content of the polyester-based elastomer and the highly polar polyester is equal to or less than a content of the cellulose fiber.

5. The molding material according to claim 1 or 2, wherein a content of the polyester-based elastomer is 400 mass % or less with respect to a content of the highly polar polyester.

6. The molding material according to claim 1 or 2, wherein the polyester-based elastomer contains, as raw material monomers, an alkyldicarboxylic acid or phthalic acid having an alkylene group with a carbon number of 2 to 8, and an alkylene diol having an alkylene group with a carbon number of 2 to 8.

7. The polyester-based elastomer contains other raw material monomers in addition to the raw material monomers, The molding material according to claim 6, wherein the other raw material monomers are one or more of styrene, butadiene, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, acetonitrile, isobutylene, isoprene, and ethylene.

8. The molding material according to claim 1 or 2, wherein the highly polar polyester has a repeating unit derived from a raw material monomer in which the number of oxygen atoms is 1 or more relative to the number of carbon atoms of 2.

9. The molding material according to claim 1 or 2, wherein the highly polar polyester comprises one or more of polylactic acid and polyhydroxybutyric acid.

10. The molding material according to claim 1 or 2, wherein the cellulose fibers have an average fiber length of less than 500 μm.

Citation Information

Patent Citations

  • Cellulose composite resin and method for producing the same

    JP2020033541A